2020
DOI: 10.1530/rep-20-0007
|View full text |Cite
|
Sign up to set email alerts
|

Placental glycogen stores and fetal growth: insights from genetic mouse models

Abstract: The placenta performs a range of crucial functions that support fetal growth during pregnancy, including facilitating the supply of oxygen and nutrients to the fetus, removal of waste products from the fetus and the endocrine modulation of maternal physiology. The placenta also stores glucose in the form of glycogen, the function of which remains unknown. Aberrant placental glycogen storage in humans is associated with maternal diabetes during pregnancy and pre-eclampsia, thus linking placental glycogen storag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 143 publications
8
56
0
1
Order By: Relevance
“…In accordance with that, it has been shown that lipid droplets formation and glycogen storage are crucial for proper trophoblast function and that p38 MAPK pathway controls the invasiveness capability of trophoblastic cells 6971 . Genes that are upregulated in clusters 1,2,3 to the highest level in OSKM reprogrammable cells are related to Wnt signaling (p≤0.008), IGF-1 pathway (p≤0.01) and cardiocyte differentiation (p≤0.0004), while cluster 4 is enriched with genes involve in BMP signaling pathway (p≤0.0001).…”
Section: Resultssupporting
confidence: 68%
“…In accordance with that, it has been shown that lipid droplets formation and glycogen storage are crucial for proper trophoblast function and that p38 MAPK pathway controls the invasiveness capability of trophoblastic cells 6971 . Genes that are upregulated in clusters 1,2,3 to the highest level in OSKM reprogrammable cells are related to Wnt signaling (p≤0.008), IGF-1 pathway (p≤0.01) and cardiocyte differentiation (p≤0.0004), while cluster 4 is enriched with genes involve in BMP signaling pathway (p≤0.0001).…”
Section: Resultssupporting
confidence: 68%
“…A number of transcriptional regulators have been implicated in regulating GlyT development and/or function [1]. We hypothesised that the transition from a predominantly glycogenic state to a glycogenolytic state during late gestation is driven by a down-regulation of genes encoding glycogenesis pathway enzymes (Fig 4) and a coincident upregulation of genes encoding glycogenolysis pathway enzymes (Fig 5).…”
Section: Temporal Expression Of Glycogenesis and Glycogenolysis Pathway Genesmentioning
confidence: 99%
“…In addition to facilitating nutrient transport from mother to fetus, the placenta also stores glucose as glycogen. Aberrant placental glycogen storage is often associated with fetal growth restriction (FGR) in mouse models [1], and in humans, elevated placental glycogen has been reported in diabetic pregnancies and pre-eclampsia [2][3][4][5][6]. However, the normal physiological role of placental glycogen stores remains unclear [reviewed in 1,7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The close proximity of glycogen trophoblasts to the vasculature suggests glycogen may exist as a source of glucose for the rapid portion of fetal growth in late gestation. 49,50 Therefore, the excess glycogen deposition, considered an indicator of developmental disturbance 49,50 , could have aided in maintaining fetal growth in the setting of IRAP deficiency.…”
Section: Irap Deficiency Perturbs Placental Development At Late Gestamentioning
confidence: 99%